2018
DOI: 10.1097/inf.0000000000001890
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Vitamin D on Seasonal Influenza A in Infants: A Multicenter, Randomized, Open, Controlled Clinical Trial

Abstract: High-dose vitamin D (1200 IU) is suitable for the prevention of seasonal influenza as evidenced by rapid relief from symptoms, rapid decrease in viral loads and disease recovery. In addition, high-dose vitamin D is probably safe for infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(74 citation statements)
references
References 28 publications
2
70
0
2
Order By: Relevance
“…The RCTs included confirmed that the respiratory tract infection was indeed derived from influenza. Only two RCTs reported beneficial effects: one among schoolchildren in Japan [52], the other among infants in China [53]. An RCT in Japan that reported no beneficial effect did not measure baseline 25(OH)D concentration [54] and included many participants who had been vaccinated against influenza (M. Urashima; private communication).…”
Section: Seasonal Influenzamentioning
confidence: 99%
“…The RCTs included confirmed that the respiratory tract infection was indeed derived from influenza. Only two RCTs reported beneficial effects: one among schoolchildren in Japan [52], the other among infants in China [53]. An RCT in Japan that reported no beneficial effect did not measure baseline 25(OH)D concentration [54] and included many participants who had been vaccinated against influenza (M. Urashima; private communication).…”
Section: Seasonal Influenzamentioning
confidence: 99%
“…The RCTs included confirmed that the respiratory tract infection was indeed from influenza. Only two RCTs reported beneficial effects: one among schoolchildren in Japan [52], the other among infants in China [53]. An RCT in Japan that reported no beneficial effect did not measure baseline 25(OH)D concentration [54] and included many participants who had been vaccinated against influenza (M. Urashima; private communication).…”
Section: Seasonal Influenzamentioning
confidence: 99%
“…These observational findings have laid the foundation for clinical trials of vitamin D supplementation for treatment or prevention of childhood respiratory tract infections, as shown in Table 6 a,b [ 155 , 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ].…”
Section: Vitamin Dmentioning
confidence: 99%
“…In 2015 Grant and colleagues analyzed the supplementation of vitamin D to pregnant women and to their infants up to 6 months of age, comparing two regimens: 1000 IU to the mothers and 400 IU to the infants vs. 200–800 IU, and found a lower proportion of children made a primary care visit for respiratory infections up to 18 months of age in the higher dose group [ 163 ]. A 2018 Chinese study tested the efficacy of vitamin D in preventing influenza A, comparing a low dose scheme (400 IU/day) vs. a high dose one (1200 IU/day) for 4 months, and reported less frequent infections in the high dose group [ 167 ].…”
Section: Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation